APLIKASI CROSS VALIDATION PADA MODEL SKILL SISWA - Wahyu Hartono (Euclid, 2020)
One of the activities in the educational test is making a diagnosis to determine whether or not a person's skills are present. This study specifically aims to design student skill models in basic mathematics courses and perform validation using a leave-one-out cross validation to select an accurate model. The diagnostic test questions used in this study ranged from moderate to difficult. The findings of this study indicate that the method of fixed test questions in order of questions from easy to difficult is better than the method of design of the initial fixed test questions. Keywords: Bayes Network, Cross Validation, Student Skill Model, Diagnostic test